A novel carrier element‐free co‐precipitation method for separation/preconcentration of lead and cadmium ions from environmental matrices. Issue 6 (25th July 2016) - Bulut, Volkan Numan; Demirci, Hamit; Ozdes, Duygu; Gundogdu, Ali; Bekircan, Olcay; Soylak, Mustafa; Duran, Celal
Abstract : A new separation and pre‐concentration method was presented in this study for two trace heavy metal ions, lead (Pb 2+ ) and cadmium (Cd 2+ ) from aqueous solutions, based on a carrier element free co‐precipitation (CEFC) method using a triazole derivate, 3‐(4‐ tert ‐butylphenyl)−5‐phenyl‐4‐(2‐hydroxy‐5‐methoxybenzylamino)−4H‐1, 2, 4‐triazole as an organic co‐precipitating agent. The method was optimized with some analytical parameters which affect the quantitative recoveries of study metals. According to the results, optimum pH of solution, quantity of co‐precipitating agent, centrifugation and incubation time, and sample volume were determined as 6.0, 1.5 mg, 10 min, and 10 min, and 100 mL, respectively. In addition, no significant matrix interferences were observed over the recovery of the metal ions. For analytical figure of merit, RSD values of the method were found as 5.7 and 4.8 for Pb 2+ and Cd 2+, respectively. LOD values were also calculated as 2.0 µg L −1 for Pb 2+ and 0.2 µg L −1 for Cd 2+ . The accuracy of method was checked with spiked/recovery tests and analysis of a standard reference material. The developed method was finally applied to the real liquid/solid samples under the optimum conditions. © 2016 American Institute of Chemical Engineers Environ Prog, 35: 1709–1715, 2016